KEEFEKTIFAN MEDIA MATEMATIKA VIRTUAL BERBASIS TEAMS GAME TOURNAMENT DITINJAU DARI COGNITIVE LOAD THEORY - Nuryadi Nuryadi (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2018)
The purpose of this study is to produce virtual mathematics learningmedia based on goodquality of TGT for use in learning mathematics and describe how well the mathematicslearning tools quality which was produced. The quality criteria used refers to the Nieveencriteria, which are valid, practical and effective. The material that was developed was thematerial of plane geometry. This research developed a mathematics learning tool using adevelopment model adapted from the ADDIE development model. The stages that need to bedone to obtain a valid, practical and effective multimedia learning mathematics is requirementanalysis and objective formulation, product design / development, trial, revision and finalproduct study. The experiments included expert trial / expert judgment, small group try-outand field try-out. The field try-out was done on two classes of VIII grade in SMP N 1 Sedayu.The research instrument used was validation sheet, teacher's appraisal sheet, studentassessment sheet, and Cognitive Load Theory (CLT) test. This research produces a qualifiedand viable virtual mathematics learning media. The results showed that multimedia learningmathematics which was developed is valid, practical and effective.